Economic activities of legal entities: problems of theory and practice - Кочин, Володимир Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The purpose of this article is to define the current view of the kinds of economic entities and their relationship with the types of legal entities and comparison with the appropriate forms of management. Starting position for research outlined issues is the definition of economic activities, establishing its relationship with the business personality of legal persons and civil juridical personality of the participants of legal relations. In economic activity refers to the activity of economic entities in the field of social production aimed at manufacturing and sale of goods, works or services of value character that have price certainty. The following analysis of economic legislation to determine the kinds of relationships covered by the concept of “economic activity”, which include economic and industrial (property and other matters arising between business entities in the course of economic activity), organizational and economic (relations between business entities and business organizational and economic powers in the management of economic activities) and internal relations (relations between structural units of the entity and the entity's relationship with its structural units. Thus, the question arises as to the limits of the concept of economic activity in general in identifying and determining the types of economic relations. Business and non-entrepreneur activity has the appropriate organizational forms, but these forms are defined as any. Thus, almost axiomatically accepted provisions entrepreneurial economic activity takes the form of companies and business enterprises and non-entrepreneur - non-entrepreneur companies. Instead, legislation defines enterprise as the organizational form of management, so enterprises can be created both for business and for non-entrepreneur (sole legally defined type of communal non-entrepreneur enterprise). In turn, recent research confirms the position that the company is not a form of non-profit activities. Thus, the analysis of legislation and scientific approaches to economic activity allows the following conclusions. First, the Economic Code of Ukraine aims to regulate business entities, i.e. their activities to create economic result that is valuable in nature and aimed at ensuring the existence of the market. Second, dichotomous division management on the business and non-entrepreneur activities require a certain view, given the nature of the activity, rather than on the legal form of the entity. Thirdly, it is necessary to outline the general principles of regulation of non-profit activities, given the current economic relations in the country. A promising area of reform of the legal regulation of economic activity, in our opinion, is not only an understanding of managing a business, reducing the number of regulatory acts and delimitation of economic law and civil law regulating the status of participants in legal relations. Fundamental principles of this process should determine the types of business entity as economic and legal category, and the legal form of legal entities, as civil category inability to legal identification.